The Economic Analysis of Venture Funds in the System of Audit - Usatenko Olga V. (Bìznes Inform, 2019)
Economic analysis is an integral part of the audit, because audit is an effective means of studying the activities of any subject, especially those engaged in the risky investment activities. Auditors in their activities should rely on the entire range of techniques and methods of economic analysis, which bears the function of evidence. Thus, the article is aimed at defining the directions of economic analysis of venture funds as part of audit in order to determine efficiency of their investment activities. The purpose of economic analysis of venture funds activity is defined, which consists in determination of efficiency of venture investments implementation, defining the directions and priority projects of investments, detection of the enabling environment for their implementation. The subjects of economic analysis of venture funds activity are defined, which include all users of analytical information, who are directly or indirectly interested in the results and achievements of investment activity of the funds. The stages of carrying out a complex system economic analysis of venture funds activity are determined. The analysis of existing methods of economic analysis of investment activity is carried out, their positive and negative sides are defined.